2021
DOI: 10.7759/cureus.20010
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Fibromyalgia, Its Concepts, and Criteria

Abstract: Fibromyalgia developed in the 1950s from a substrate of difficult to explain regional and widespread pain mixed with symptoms of psychosocial distress. Controversies regarding psychological issues were common. Multiple criteria arose to define the disorder, but each identified a different set of patients. The identification of widespread pain as a criterion changed the nature of the disorder by effectively eliminating regional pain as a component condition. The easy-to-measure and relatively reliable widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 75 publications
0
21
0
1
Order By: Relevance
“…Furthermore, one question arises: What is the difference between persons with PSD scores of 10 and those with PSD scores of 12? It has been shown that persons who do not meet FM criteria but have mild (scores 4-7) and moderate (scores 8-11) PSD scores have substantial symptomatic burdens and an increase in adverse outcomes (6). Therefore, it appears that diagnosing this condition at the lower severity score is not a weak point of our study, but rather, it indicates that we should not delimit FM diagnosis to scores used in the existing criteria.…”
mentioning
confidence: 80%
“…Furthermore, one question arises: What is the difference between persons with PSD scores of 10 and those with PSD scores of 12? It has been shown that persons who do not meet FM criteria but have mild (scores 4-7) and moderate (scores 8-11) PSD scores have substantial symptomatic burdens and an increase in adverse outcomes (6). Therefore, it appears that diagnosing this condition at the lower severity score is not a weak point of our study, but rather, it indicates that we should not delimit FM diagnosis to scores used in the existing criteria.…”
mentioning
confidence: 80%
“…Researchers still do not recommend first-line drug treatment but have gradually begun to recognize the role played by alternative medicines in treatment, such as acupuncture. In recent years, Sarzi-Puttini, 47 Wolfe, 48 Maffei, 49 and Galvez-Sánchez 50 have published their opinions and relevant research results on the revision of diagnostic and therapeutic criteria for FMS, and researchers believe that a combination of protocols should be used to develop individualized treatment. The burst intensity of melanoma and core needle biopsy is second only to the criteria, demonstrating that accompanying symptoms related to FMS, such as, tumors, also have the potential to become a hot spot for new research in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of FM continues to be debated. However, it has been demonstrated that fibromyalgia is independent of its comorbidities and FM patients suffer from other pathologies in parallel [ 7 , 8 ]. In the same way, some researchers consider FM to be a neurobiological disease caused by abnormal pain processing [ 9 ].…”
Section: Introductionmentioning
confidence: 99%